El Cometimiento de una Infracción cuando se encuentre declarado el Estado de Excepción debe ser Tipificado como Circunstancia Agravante en el Código Orgánico Integral Penal - Rojas Delgado, Patricia Anabelle (2016)
In this thesis entitled "the commission of a violation once FIND declared a state of emergency must be characterized as an aggravating circumstance INTEGRAL ORGANIC PENAL CODE", the issues raised goes that currently Ecuadorian society is immersed under Presidential Decree state of emergency which limits certain rights to individuals, and powers to the President to create standards for the good of the reason for the declaration, which in our case is the earthquake. The government was forced to issue this measure already available to the security forces in coordination with the Ministry of the Interior should be responsible for social prevention, ie care in society of crime, and to lock every individual is found committing crimes. Faced with this declaration of state of emergency, some individuals have been caught committing crimes, taking advantage authorities are concentrated their participation in the earthquake disaster. These people do not mind the misfortune of other human beings, and proceed to commit crimes, so, my concern over these crimes that should be tried immediately and the maximum penalty provided for the offense or contravention should be imposed on them. Therefore, it is my concern that must be typed in Art. 47 of the Code of Criminal Integral, as a general aggravating circumstance for any offense the imposition of the maximum penalty for each offense. The Constitution seeks to protect human rights of people, allowing the legality of the state of emergency, however, there are many people who takeadvantage of public calamities or natural disasters to commit crimes and undermine civil peace; despite exist in the Code of Criminal Integral circumstances aggravating sentencing in cases where offenders prey on mass gatherings, riot, popular commotion, sporting event or public calamity, a phenomenon of nature to run the offense. This criminal standard is not well defined the legal elements of the state of emergency that may impose the most severe penalty of the offense of crime committed in a declared state of emergency, so you should be rationed in the Code of Integral Penal and determine their legal elements in the Law of Public security and the State, in order to guarantee peace and public security. To fulfill this investigation we have taken the following criteria: For Victor Garcia Toma, about the state of emergency, said: "this sense refers to those" skills crisis "that the Constitution gives the State as extraordinary, to effects that you can face facts, events or events which, by their nature, endanger the normal functioning of public authorities or threaten the continuity of state institutions and the basic principles of coexistence within a political community. " According to the author Eduardo Noboa about the aggravating circumstance of the violation states: "The legislator builds its punitive provisions on the basis of a description as accurate as possible of the behaviors chosen to originate in principle criminal liability". I have relied on the doctrine in the field of research concluding that it is necessary to propose a draft reform of the Organic Code Integral Penalbecause lacks legal rules, to allow guarantee full right of people in a state of emergency, being necessary to establish own legal elements of the state of emergency in the penal system, as an aggravating circumstance of the offense.